Manhaj al-Imam al-Bukhari fi kitabihi al-Du'afa' : dirasah nazariyah tatbiqiyah = Methodology of Imam al-Bukhari in his book al-Du'afa : theory and practical study / Salem Saleh Ahmed al-Ammari - Salem Saleh Ahmed, Ammari (2012)
The study aims at knowing Imam Bukhari’s methodology in his book, Al-dhuafa, and knowing the methods of classification the Imams of Sunnah adopted. This knowledge offers great benefits so that we become aware of the nature of Sunnah sciences and how they originated, and refutes the suspicions of those who condemn the Prophetic Sunnah because of their ignorance. The research involves an introduction, four chapters and a conclusion. In the introduction, the researcher gave a glimpse about Imam Bukhari and his status in the science of scholars’ description. The first chapter is a general description of the book, Al-dhuafa, and in the second chapter, the researcher tries to bring out the manifestations of hadith criticism for the chain of narrators and the texts in the book, Al-dhuafa. The last two chapters of the applied study are dedicated to some of the narrators whose biography Imam Bukhari had been criticized for. The researcher titled the third chapter ‘The Sahabah and Their Good Characters, the Ways to Prove Their Companionship’, and titled the fourth chapter ‘the Bukhari’s Chosen Narrators He Mentioned in his Book, Al-dhuafa while he Included Their Narrations in His Sahih-ul-Bukhari’. He concluded the study with the most important findings, recommendations and indexes, and supplemented it with many appendices. The researches hopes to achieve several objectives of this study, most notably: first, stating Imam Bukhari’s methodology in his writing the weak; second: refuting the scientific controversies about the book and the subsequent degradation in the authentic Sunnah and its carriers; and third: highlighting what the Al-dhuafa contains of the beneficial precepts in the field of the two branches of the science of Hadith: criticism and recommendation.